PENGARUH TAYANGAN TELEVISI EDUKATIF SI BOLANG DENGAN NILAI KEHIDUPAN: KAJIAN SOSIOLOGI SASTRA - Nurjannah, Nurjannah; Ramasari, Putri; Nasution, Putridary Aprillia; Aspinda, Lili; Anjani, Sri Retno (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2024)
This research examines the influence of the educational television show “Si Bolang” on life values through a literary sociology perspective. “Si Bolang” is a children’s program that shows the adventures of a child in exploring cultural diversity and local wisdom in various regions of Indonesia. By using content analysis methods and in-depth interviews, this research aims to identify the social, cultural and moral values represented in these shows and their impact on the understanding and behavior of viewers, especially children. The research results show that “Si Bolang” effectively conveys values such as mutual cooperation, tolerance, love of the environment, and respect for local wisdom. This show also plays a role in forming awareness of multiculturalism and national identity in its viewers. This research provides insight into the potential of mass media, especially educational television programs, in transmitting positive values and shaping the character of Indonesia’s young generation.